2018
DOI: 10.1016/j.sxmr.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytosis Following Testosterone Therapy

Abstract: Short-acting injectable testosterone is associated with greater risk of erythrocytosis compared with other formulations. The mechanism of the pathophysiology and its role on thromboembolic events remain unclear, although some data support an increased risk of cardiovascular events resulting from testosterone-induced erythrocytosis. Ohlander SJ, Varghese B, Pastuszak AW. Erythrocytosis Following Testosterone Therapy. Sex Med Rev 2018;6:77-85.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 87 publications
1
96
1
3
Order By: Relevance
“…In addition, trans men on testosterone undecanoate exhibited lower erythrocytosis rates (9.2% were >50 Hct %, and 0 were >52 Hct %), compared to trans men on testosterone esters (15.9% were >50 Hct %, and 6.8% were >52 Hct %) or gel (12.8% were >50 Hct %, and 2.6% were >52 Hct %). We were not able to correlate this finding with differences in testosterone levels, which might be explained by the fact that pharmacokinetic profiles of these formulations mostly differ with respect to peak concentrations and overall stability of serum concentrations (Ohlander et al ., ), parameters which were not measured in our study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, trans men on testosterone undecanoate exhibited lower erythrocytosis rates (9.2% were >50 Hct %, and 0 were >52 Hct %), compared to trans men on testosterone esters (15.9% were >50 Hct %, and 6.8% were >52 Hct %) or gel (12.8% were >50 Hct %, and 2.6% were >52 Hct %). We were not able to correlate this finding with differences in testosterone levels, which might be explained by the fact that pharmacokinetic profiles of these formulations mostly differ with respect to peak concentrations and overall stability of serum concentrations (Ohlander et al ., ), parameters which were not measured in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Comparative studies in hypogonadal men have shown that the rate of erythrocytosis is higher in men receiving short‐acting intramuscular injections, compared to transdermal or subcutaneous routes (Dobs et al ., ; Pastuszak et al ., ). An explanation might be found in the fact that short‐acting intramuscular injections cause a rapid supraphysiological peak shortly after injection, decreasing to low levels when the next injection is near, whereas transdermal systems and pellets result in more stable serum concentrations (Ohlander et al ., ). Administration of testosterone undecanoate, an oil vehicle‐based formulation which is injected intramuscularly every 12 weeks, results in more stable serum concentrations than intramuscular injections with testosterone esters (Schubert et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Patients on IM therapy are at highest risk of erythrocytosis and, therefore, continued monitoring of HCT is most important in this subgroup. 23 Consideration should be given to switching these patients, particularly those who are already demonstrating signs of erythrocytosis, to lower doses or to topical agents. 24…”
Section: Virtual Visitmentioning
confidence: 99%
“…Clearly, given data linking elevated haematocrit levels with increased morbidity/mortality, an evidence-based threshold value that can be used in clinical practice is needed. A further issue in using TTh may be the testosterone preparation and its mode of delivery[28]. A recent comprehensive review suggested short-acting, injectable testosterone is associated with greater risk of elevated haematocrit compared with other preparations[28].…”
mentioning
confidence: 99%
“…A further issue in using TTh may be the testosterone preparation and its mode of delivery[28]. A recent comprehensive review suggested short-acting, injectable testosterone is associated with greater risk of elevated haematocrit compared with other preparations[28]. This raises the possibility that the rate of change in serum testosterone concentration may be mechanistically important; short-acting injectable testosterone could lead to steeper rises and falls in hormone levels that in turn has effects on erthrocytosis.…”
mentioning
confidence: 99%